Steroidal aromatic Naphthenic Acids in oil sands process-affected water: Structural comparisons with environmental estrogens - Rowland, S.; West, C.; Jones, D.; Scarlett, Alan; Frank, R.; Hewitt, L. (2011)
The large volumes, acute toxicity, estrogenicity, and antiandrogenicity of process-affected waters accruing in tailings ponds from the operations of the Alberta oil sands industries pose a significant task for environmental reclamation. Synchronous fluorescence spectra (SFS) suggest that oil sands process-affected water (OSPW) may contain aromatic carboxylic acids, which are among the potentially environmentally important toxicants, but no such acids have yet been identified, limiting interpretations of the results of estrogenicity and other assays. Here we show that multidimensional comprehensive gas chromatography-mass spectrometry (GCxGC-MS) of methyl esters of acids in an OSPW sample produces mass spectra consistent with their assignment as C 19 and C20 C-ring monoaromatic hydroxy steroid acids, D-ring opened hydroxy and nonhydroxy polyhydrophenanthroic acids with one aromatic and two alicyclic rings and A-ring opened steroidal keto acids. High resolution MS data support the assignment of several of the so-called O3 species. When fractions of distilled, esterified, OSPW acid-extractable organics were examined, the putative aromatics were mainly present in a high boiling fraction; when examined by argentation thin layer chromatography, some were present in a fraction with a retardation factor between that of the methyl esters of synthetic monoalicyclic and monoaromatic acids. Ultraviolet absorption spectra of these fractions indicated the presence of benzenoid moieties. SFS of model octahydro- and tetrahydrophenanthroic acids produced emissions at the characteristic excitation wavelengths observed in some OSPW extracts, consistent with the postulations from ultraviolet spectroscopy and mass spectrometry data. We suggest the acids originate from extensive biodegradation of C-ring monoaromatic steroid hydrocarbons and offer a means of differentiating residues at different biodegradation stages in tailings ponds. Structural similarities with estrone and estradiol imply that such compounds may account for some of the environmental estrogenic activity reported in OSPW acid-extractable organics and naphthenic acids. © 2011 American Chemical Society.